2016
DOI: 10.1016/j.njas.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of milk quota abolishment on farm intensity: Shifts and stability

Abstract: We investigate whether milk quota abolition in the Netherlands is likely to lead to a shift towards more intensive farms, and whether the legislation introduced by the Dutch government to prevent this from happening is likely to be effective. To this end, a mathematical programming model is developed and applied to ten Dutch dairy farms of varying size. The mathematical programming model allows us to calculate shadow prices, which we use to evaluate the stability or likelihood of a shift in the farmer decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 22 publications
4
31
0
1
Order By: Relevance
“…The findings of the current study, as confirmed by previous researchers, showed that producers work within a tightly constrained and regulated environment limiting their ability to determine the future of their farm according to their personal desires. This [31] showed that bigger farms are more likely to increase than other farms.…”
Section: Production Factorsmentioning
confidence: 93%
“…The findings of the current study, as confirmed by previous researchers, showed that producers work within a tightly constrained and regulated environment limiting their ability to determine the future of their farm according to their personal desires. This [31] showed that bigger farms are more likely to increase than other farms.…”
Section: Production Factorsmentioning
confidence: 93%
“…However, the intensification of dairy farming has also raised environmental concerns driven by increased manure production, as well as animal welfare concerns, such as increased lameness or unethical disposal of male calves. In the Netherlands, this has evolved into a societal debate that led to the implementation of a measure in September 2015 that restricts the further intensification of dairy farming (Groeneveld et al ., ). This legislation will most likely increase the importance of farm size for further expansion and limit intensification in the Netherlands, as farms are required to purchase additional land if they want to increase their dairy production.…”
Section: Implications For Sustainable Intensification Policymentioning
confidence: 97%
“…However, the intensive nature of the Dutch dairy system has raised concerns especially regarding manure application; this is because EU dairy farming is bound by environmental regulations through the EU Nitrates directive that limits the amount of nitrogen and phosphate that can be put on the land. Consequently, the Dutch government implemented the ‘Dairy Law’ in January 2015 to prevent further excesses of nitrogen and phosphate on farms (Groeneveld et al ., ).
…”
mentioning
confidence: 97%
“…In April 2015, the EU milk quota system was abolished, both in response to an increasing global demand for milk and agreements on trade liberalisation in global dairy markets (EU 2015). Small farmers, farmers in mountain areas or those with higher production costs are very likely going to suffer without the protection of the quota system (Groeneveld et al 2016).…”
Section: Introductionmentioning
confidence: 99%